Contradictions of Medical Tourism - Martin Zsarnoczky (DETUROPE)
Industries have to face continuously emerging new trends and challenges worldwide. The former pattern of local bundling techniques cannot seem to be adapted at global measures. The processes of globalisation urgently call for the harmonisation of legislative policies and practices. A good example for this is the current situation of health tourism. In the most rapidly changing industry, development has overcome legislation by far, and unfortunately left policy makers and local stakeholders unable to respond to the new challenges. However, the continuous growing on the demand side forecasts further massive development of the field in the coming decades. My research focuses on this contradictory situation: I try to find out whose responsibility is it to force the creation of a unified legal background: the supply side that offers a wide variety of different services or the rather vulnerable supply side that needs a transparent quality assurance system to be protected.